Brown gold of marginal soil: Plant growth promoting bacteria to overcome plant abiotic stress for agriculture, biofuels and carbon sequestration - Ramakrishna, Wusirika; Rathore, Parikshita; Kumari, Ritu; Yadav, Radheshyam (The Science of the total environment, 2020)
[Display omitted] •Marginal soil is an untapped resource which can be exploited using plants and bacteria.•Some PGPB enhance abiotic stress (drought, salinity and heavy metals) tolerance.•Molecular approaches employed by plant-soil-PGPB interactions crucial for the success.•Efficient utilization of marginal soil will enhance crop productivity and soil remediation. Marginal land is defined as land with poor soil characteristics and low crop productivity with no potential for profit. Poor soil quality due to the presence of xenobiotics or climate change is of great concern. Sustainable food production with increasing population is a challenge which becomes more difficult due to poor soil quality. Marginal soil can be made productive with the use of Plant Growth Promoting Bacteria (PGPB). This review outlines how PGPB can be used to improve marginal soil quality and its implications on agriculture, rhizoremediation, abiotic stress (drought, salinity and heavy metals) tolerance, carbon sequestration and production of biofuels. The feasibility of the idea is supported by several studies which showed maximal increase in the growth of plants inoculated with PGPB than to uninoculated plants grown in marginal soil when compared to the growth of plants inoculated with PGPB in healthy soil. The combination of PGPB and plants grown in marginal soil will serve as a green technology leading to the next green revolution, reduction in soil pollution and fossil fuel use, neutralizing abiotic stress and climate change effects.